Taming of the Demons Violence and Liberation in Tibetan Buddhism - Dalton, Jacob Paul 1969- (New Haven Yale University Press, 2011)
Cover -- Contents -- Acknowledgments -- Introduction -- ONE: Evil and Ignorance in Tantric Buddhism -- TWO: Demons in the Dark -- THREE: A Buddhist Manual for Human Sacrifice? -- FOUR: Sacrifice and the Law -- FIVE: Foundational Violence -- SIX: Buddhist Warfare -- SEVEN: Conclusions: Violence in the Mirror -- Appendix A. The Subjugation of Rudra -- Appendix B. Dunhuang Liberation Rite (Transcription of PT42/ITJ419) -- Appendix C. Dunhuang Liberation Rite II (Translation and Transliteration of PT840/1) -- Notes -- Glossary of Tibetan Titles and Terms -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y -- Z.
""Bibliography""""Index""; ""A""; ""B""; ""C""; ""D""; ""E""; ""F""; ""G""; ""H""; ""I""; ""J""; ""K""; ""L""; ""M""; ""N""; ""O""; ""P""; ""Q""; ""R""; ""S""; ""T""; ""U""; ""V""; ""W""; ""X""; ""Y""; ""Z""
Description based upon print version of record
Keywords: Tantric Buddhism -- China -- Tibet Autonomous Region; Electronic books; Tantric Buddhism ; China ; Tibet Autonomous Region; Violence ; Religious aspects ; Tantric Buddhism; Electronic books